2017
DOI: 10.1002/mrm.26924
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of exogenous and endogenous CESTMRI methods for evaluating in vivo pH

Abstract: Measurements of k with endogenous CEST MRI cannot substitute for pHe measurements with acidoCEST MRI. Whereas endogenous CEST MRI may still have good utility for evaluating some specific pathologies, exogenous acido-CEST MRI is more appropriate when evaluating pathologies based on pHe values. Magn Reson Med 79:2766-2772, 2018. © 2017 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 43 publications
3
41
0
Order By: Relevance
“…14 In this respect, it is worth mentioning that there was no correlation between the amide proton exchange rate and extracellular pH measured in an exogenous contrast agent-based CEST experiment (acidoCEST). 75 As shown recently, 14,76 the increased protein content in the tumor is the most likely explanation, because only a small intracellular pH increase (<0.1 unit) is often detected. The results are consistent with increasing protein concentrations in malignant tumors, as revealed by MRI-guided proteomics 77,78 and in vivo MR spectroscopy.…”
Section: Current Applicationsmentioning
confidence: 84%
See 1 more Smart Citation
“…14 In this respect, it is worth mentioning that there was no correlation between the amide proton exchange rate and extracellular pH measured in an exogenous contrast agent-based CEST experiment (acidoCEST). 75 As shown recently, 14,76 the increased protein content in the tumor is the most likely explanation, because only a small intracellular pH increase (<0.1 unit) is often detected. The results are consistent with increasing protein concentrations in malignant tumors, as revealed by MRI-guided proteomics 77,78 and in vivo MR spectroscopy.…”
Section: Current Applicationsmentioning
confidence: 84%
“…Theoretically, the APTw hyperintensity in glioma can be caused by increased cytosolic protein content or increased intracellular pH . In this respect, it is worth mentioning that there was no correlation between the amide proton exchange rate and extracellular pH measured in an exogenous contrast agent‐based CEST experiment (acidoCEST) . As shown recently, the increased protein content in the tumor is the most likely explanation, because only a small intracellular pH increase (<0.1 unit) is often detected.…”
Section: Current Applicationsmentioning
confidence: 93%
“…Recent reports have indicated that the concentration dependence dominates the pH dependence of endogenous APT CEST MRI . Also, endogenous CEST measures a combination of intracellular and extracellular pH, while tumor acidosis predominately affects only extracellular pH, reducing the sensitivity of endogenous CEST MRI for tumor acidosis . Therefore, the pH dependence of endogenous CEST MRI may contribute to localizing acidic tumors, but current endogenous CEST MRI methods are insufficient to quantitatively measure tumor pH.…”
Section: Acidocest Mrimentioning
confidence: 99%
“…The MRI contrast of these probes can be analyzed by using a ratiometric approach, thanks to which pHe can be assessed independently of knowing the actual probe concentration . Both diamagnetic and paramagnetic CEST molecules have been reported for such applications …”
Section: Introductionmentioning
confidence: 99%
“…29 Both diamagnetic and paramagnetic CEST molecules have been reported for such applications. [30][31][32][33][34][35][36] Recently, YbHPDO3A (ytterbium 1,4,7-triscarboxymethyl-1,4,7,10-tetraazacyclododecane) has been investigated for this purpose. 37 This chemical compound is analogous to a clinically approved molecule (GdHPDO3A, gadolinium 1,4,7-triscarboxymethyl-1,4,7,10tetraazacyclododecane, ProHance from Bracco Imaging) in which gadolinium (Gd) is replaced by ytterbium (Yb).…”
mentioning
confidence: 99%